The Impact of Customer Success Factors on the Financial Performance of International Computer Technology Companies in Dubai - et. al., Basel Qasem Radwan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Continuous enhancement of organizational performance is indispensable for every organization, most especially in this more challenging economic period. Substantial studies have been conducted to unravel and explain the drivers of enhanced performance, but very few studies have examined the effects of customer success management on organizational performance, despite its positive role in the performance enhancement. Therefore, this study investigates the effect of customer success management, involving integration of customer management, personnel capabilities, and customer orientation, on financial performance of international computer technology companies in Dubai, United Arab Emirates. Using the cross-sectional research approach, data were collected from a sample of 150 managers from Dubai international computer technology companies. Partial Least Squares Method (PLS) algorithm and the bootstrapping technique were used to test the study’s hypotheses. The overall findings signified that integration of customer management models, personal capabilities and customer orientation would have positive effects on performance, indicating that customer success is key and essential to enhance the organizational performance of the international computer technology companies in Dubai. To earn greater financial performance level, the international computer technologies companies should put more focus on satisfying and fulfilling their customers’ expectations. Thus, this study has offered some noteworthy contributions to the body of knowledge and some significant implications for policymakers and stakeholders.